2022
DOI: 10.3390/jpm12040640
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of SARS-CoV-2 IgG Spike Antibody Responses on Admission and Clinical Outcomes of COVID-19 Disease in Fully Vaccinated Inpatients: The CoVax Study

Abstract: Background: SARS-CoV-2 vaccines have shown high efficacy in protecting against COVID-19, although the determinants of vaccine effectiveness and breakthrough rates are yet to be determined. We aimed at investigating several factors affecting the SARS-CoV-2 IgG Spike (S) antibody responses on admission and clinical outcomes of COVID-19 disease in fully vaccinated, hospitalized patients. Methods: 102 subjects were enrolled in the study. Blood serum samples were collected from each patient upon admission for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Within the framework of the CoVax study, 3 in this substudy we enrolled 51 hospitalized Greek patients (41 male and 10 female, mean age 79.5±1.6 y) with COVID-19 disease as confirmed by means of real time polymerase chain reaction (RT-PCR). All subjects had received three doses of the Pfizer-BioNTech vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…Within the framework of the CoVax study, 3 in this substudy we enrolled 51 hospitalized Greek patients (41 male and 10 female, mean age 79.5±1.6 y) with COVID-19 disease as confirmed by means of real time polymerase chain reaction (RT-PCR). All subjects had received three doses of the Pfizer-BioNTech vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…However, a large study from central Greece after the prevalence of new variants of the virus (Delta and Omicron) demonstrated that vaccination was still effective and provided high protection in terms of mortality and the clinical severity of COVID-19 [ 6 ]. Nevertheless, even in fully vaccinated patients, older age, higher viral load and a shorter period between symptom onset and hospital admission were associated with absence of anti-S SARS-CoV-2 antibodies upon hospital admission and poor clinical outcomes [ 7 ]. On the other hand, individuals vaccinated against COVID-19, but who were still infected by the virus, showed an “excellent boost” in their immune response [ 8 ].…”
mentioning
confidence: 99%